Reliability and Validity of HIV Self-Reported Result in Determining HIV Prevalence in a Region with High HIV Prevalence - Asadhi, Elijah Otieno (JOOUST, 2016)
Studies of health care outcomes and HIV intervention programs depends on HIV results to accurately enroll HIV positive people in intervention programs. While- several studies have been done around HIV self-reported result, there is still a paucity of data on the reliability and validity of data from self-reported HIV result. This study sought to determine the reliability and validity of self-reported HIV result in a region with high HIV burden. This study used a prospective cohort study design. A random sample of participants aged 15-64 years living in Gem Sub-County were enrolled and later followed up within one year for testing. A total of 5955 respondents were considered for this analysis, 63.5% were women and 36.5% men. HIV prevalence among the sampled population was 15.4%, the burden of HIV was relatively high among women (16.2%) compared to men (12.1 %). Agreement between self-reported and actual HIV result was 96.9% with a very good Cohen's kappa of 0.869(95%CJ= 0.8501 - 0.8874). Males (kappa= 0.874, 95%CJ 0.841 - 0.907) presented slightly higher agreement than women (kappa= 0.866, 95%CJ 0.843 - 0.889). The sensitivity of HIV self-reported result was 0.81, 95%CI (0.784 -0.836) and a specificity of 0.997, 95%CJ (0.995-0.998) with an accuracy of 0.97, 95%CI (0.965-0.974). HIV self-reported result had a higher positive predictive value of 0.978, 95%CI (0.964-0.987) with a comparatively slightly lower negative predictive value of 0.968, 95%CI (0.963-0.973). Those aged 45 - 49 years (OR 11.19 95%CI 3.641 - 34.413), had knowledge of partner's HIV status (OR= 3.44, 95%CI 2.290 - 5.192, p<0.001) and tested previously as couples (OR= 0.47, 95%CI 0.271 - 0.817, p = 0.007) had a statistically significant increased odds of correctly reporting their HIV status. In conclusion, self-reported positive status provides an accurate measure of HIV status, hence self-reported sero-positivity should be treated as HIV positive for purposes of surveillance and equally for inclusion into interventions which require HIV positive individuals.